Mutations in TERT promoter and FGFR3 and telomere length in bladder cancer. Issue 7 (7th April 2015) - Hosen, Ismail; Rachakonda, P. Sivaramakrishna; Heidenreich, Barbara; de Verdier, Petra J.; Ryk, Charlotta; Steineck, Gunnar; Hemminki, Kari; Kumar, Rajiv
<x xml:space="preserve">Abstract</x> Mutations in the promoter of the telomerase reverse transcriptase (TERT) and fibroblast growth factor receptor 3 (FGFR3) genes constitute the most recurrent somatic alterations in urothelial carcinoma of bladder. In this study, we screened DNA from 327 urothelial bladder carcinomas from well‐documented patients, with different stages and grades and known TERT promoter mutational status, for FGFR3 alterations and measured relative telomere length (RTL). Although, the frequency of the TERT promoter mutations was higher than those in FGFR3; however, the alterations at the two loci occurred together more frequently than per chance [Odds ratio (OR) = 4.93, 95% CI = 2.72–8.92, p < 0.0001]. While tumors with TERT promoter and FGFR3 mutations had shorter RTL than those without mutations (p < 0.0001), the TERT promoter mutations in conjunction with the common allele of the rs2853669 polymorphism defined sub‐group of patients with an observed decreased overall survival (OR = 2.15, 95% CI = 1.00–4.61) and increased recurrence in patients with TaG1+TaG2 disease categories (OR = 3.68, 95%CI = 1.12–12.05). The finding of shorter telomeres in tumors with TERT promoter and/or FGFR3 mutations than without mutations implies mechanistic relevance of telomere biology in cancer progression. The observed association with recurrence and survival shows that the TERT promoter mutations can potentially be used as markers to refine selection of patients for different treatments. The overwhelming frequency of the TERT promoter mutations also represents a case for development of an eventual therapeutic target.